Ferroelectric-mediated filamentary resistive switching in P(VDF-TrFE)/ZnO nanocomposite films. Issue 23 (4th June 2018) - Kim, Tae Yeon; Anoop, Gopinathan; Son, Yeong Jun; Kim, Soo Hyeon; Lee, Eunji; Jo, Ji Young
Abstract : Organic ReRAMs based on ferroelectric P(VDF-TrFE) and ZnO NPs blends exhibiting bipolar resistive switching and a high ON/OFF ratio were realized using a low-cost solution process. Abstract : In ferroelectric (FE) polymer–semiconducting polymer blend based organic resistive random access memory devices (ReRAM), the carriers are injected into the semiconductor region of the blend because of the polarization originated internal electric field in the FE polymer. A higher concentration of semiconducting polymer in the FE polymer–semiconducting polymer blends usually generate a high leakage current and degrades the FE characteristics of the FE polymer resulting in a high OFF current and consequently a low ON/OFF ratio. In order to achieve a high ON/OFF ratio in the FE polymer/semiconducting polymer blends, the FE properties of the FE polymer should be preserved. In this study, organic ReRAMs based on ferroelectric poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) and ZnO nanoparticle (NPs) blends exhibiting bipolar resistive switching and a high ON/OFF ratio were realized using a low-cost solution process. Unlike conventional ferroelectric polymer–semiconducting polymer blend systems where FE characteristics are suppressed in ReRAMs, our Au/P(VDF-TrFE)_ZnO NPs/n ++ Si devices retain the FE characteristics of the P(VDF-TrFE) polymers. Our devices switch between bi-stable resistance states via the ferroelectric-assisted filamentary conduction mechanism. Based on ex situ transmission electron microscopy and elemental mapping analyses, we found that the resistive switching occurs through the formation of conduction paths consisting of Zn-rich/F-deficient regions. The device fabricated at a blend ratio of 20 wt% ZnO NPs in P(VDF-TrFE) matrix exhibited optimal stable resistive switching behavior with an ON/OFF ratio of up to 2 × 10 7 and a retention time of 10 4 s.